Culturas de cobertura, residual de nitrogênio e reaplicação de calcário em sistema plantio direto: cultura da soja - Rodrigues, Leandro Rebuá [UNESP] (2012)
No-tillage (NT) is a widely used practice of cultivation in Brazil, and the dynamics of soil acidity and maintenance of the straw in Savannah in this system need to be further investigated and elucidated. Given the context, this study aimed to evaluate changes in soil chemical characteristics and agronomic traits of soybean as a function of cover crops, residual nitrogen and lime rates reapplied to the surface, where an area with no-tillage system has been established for eight years . The study was conducted at experimental area UNESP – Ilha Solteira Campus, which began in crop year 2000/01 with the implementation of no-tillage. In crop year 2001/02, began the four modes of application of lime and a control treatment without lime application, using cover crops in Spring. In crop year 2003/04, is subdivided parcels for the installation of treatments with three nitrogen rates (0, 90 and 180 kg ha-1) and succeeded soybeans by corn. Soybean has become the main crop again in 2006/07 and 2007/08 harvest was performed reapplication of lime surface, calculated according to the results of chemical analysis of soil obtained in 2006. This paper refers to the agricultural year 2008/09, which had the seeding of cover crops (pearl millet and sunn hemp) in October and in succession (December 2008), the soybean cultivar BR / MG 68 (Vencedora), was sown at a spacing of 0.45 m between rows and 12 kg of N, 60 kg of P2O5 and 60 kg of K2O per hectare was used at planting. In the soybean crop was rated the initial and final population, nodulation, nutritional status of plants in full bloom, agronomic characteristics, mass of 1000 grains and grain yield. After soybean harvest, soil samples were collected in layers of 0.00 to 0.05, 0.05-0.10, 0.10-0.20 and 0.20-0.40 m depth and evaluated the following chemical characteristics: pH, OM, P, K, Ca, Mg and base saturation. OM increases until the layer of 0.20 – 0.40 m of ...